Searches for supersymmetry and exotics phenomena with the ATLAS detector - Robichaud-Véronneau, A (2013)
Searches for new physics beyond the Standard Model are performed using the p-p LHC data collected with the ATLAS detector in 2011 at 7 TeV and in 2012 at 8 TeV centre-of-mass energy. Various production modes for supersymmetric (SUSY) particles are considered: strong production of squarks and gluinos, weak production of sleptons and gauginos, R-parity violating decays and long-lived particles. No significant deviation from the Standard Model processes is observed and limits are set on different flavours of SUSY, such as cMSSM/mSUGRA, pMSSM, GMSB and AMSB. Searches for exotic models for BSM physics are performed, probing for a large variety of well-motivated models, such as heavy gauge resonances, excited fermions, extra-dimensions, exotic Higgs models and new quarks. As in the case of SUSY searches, no excess is observed above the SM background and limits are obtained for the models mentioned above. © 2013 IOP Publishing Ltd.